Hubungan Pengetahuan Mahasiswa Ilmu Keolahragaan dengan Perilaku Penggunaan Tabir Surya untuk Melindungi Kulit dari Paparan Radiasi Ultraviolet - Nabella Prameswari, Yuda; Nazwa Syifa; Baety Adhayati; PRAMESWARI, YUDA (Calvaria Medical Journal, 2026)
Background: Ultraviolet (UV) radiation increases the risk of skin disorders, particularly among individuals engaged in outdoor activities. Despite the proven effectiveness of sunscreen, the relationship between knowledge and sunscreen use among Sports Science students in Indonesia remains unclear. Objectives: This study aims to analyze the relationship between the level of knowledge and sunscreen usage behavior among students of the Sports Science Study Program at Sultan Ageng Tirtayasa University. Methods: This research employed an analytical observational study with a cross-sectional design involving 77 students from the Sports Science Study Program at Sultan Ageng Tirtayasa University. Participants were selected using a consecutive sampling technique. Data were collected through a validated questionnaire and analyzed using the Chi-Square test with a 95% confidence level. Results: A total of 71.4% of respondents demonstrated good knowledge about sunscreen, and 80.5% exhibited good sunscreen usage behavior. A significant relationship was found between knowledge level and sunscreen use behavior (p < 0.001). Students with lower sunscreen-related knowledge had 12.75 times higher odds of demonstrating poor sunscreen use behavior compared to students with higher knowledge levels (OR = 12.75; 95% CI: 3.41 – 47.57). Among the confounding variables analyzed, only gender showed a significant association with sunscreen use behavior (p = 0.028). Conclusions: Knowledge level is significantly associated with sunscreen usage behavior among Sports Science students. Comprehensive education about sunscreen is essential to enhance protective behavior against UV exposure. Further research is recommended to explore other influencing factors such as attitudes and environmental influences on sunscreen use.